Review Article on Recent Development in Hepatitis C - varuna, K M (International Journal of Pharmaceutical & Biological Archive, 2010)
The biological differences between genotypes make genotyping important for decision-making regarding disease management and therapeutic intervention. HCV infection is estimated to be the commonest liver disease in renal dialysis patients with a prevalence rate of 5% to as high as 50% in some centers. Most natural hepatitis C virus (HCV) infection elicits poor immune responses and 75% to 85% of HCV infections become chronic; therefore, the development of an effective vaccine is of paramount importance. HCV was discovered in 1988. Hepatitis C virus (HCV) is a major cause of chronic hepatitis worldwide, which finally leads to development of hepatocellular carcinoma. Hepatitis C virus (HCV) translation initiation depends on an internal ribosome entry site (IRES). Previously we will study the detail and treatment of HCV. Hepatitis C virus (HCV) causes persistent infection and induces chronic hepatitis, liver cirrhosis and finally hepatocellular carcinoma. Current therapies for HCV infection have not been satisfactory, and more effective anti-viral treatments are needed. Despite progressive advances, therapy with interferon and ribavirin has been the mainstay of treatment for chronic hepatitis C for over a decade. Therefore, the development of further effective therapeutic agents against HCV is an urgent public health requirement. Anti-HCV activity of certain 50-O-masked analogues would arise from a new type of mechanism that does not involve the 50-O-triphosphorylation process. There is still room for the discussion on the 50-O-masking effect because certain carbon–oxygen bonds, for example, the carboxylic ester bond of compound (i.e., the benzoate moiety in compound) are often hydrolyzed in cultured cells.